PERAN ORANG TUA DALAM MENERAPKAN METODE-METODE PENDIDIKAN ISLAM ANAK USIA DINI SELAMA BELAJAR DI RUMAH - Puspitaloka, Viny Anggradini; Munastiwi, Erni; Irbah, Ariq Nurjannah; Maulida, Nelvi; Mustika, Nadha (Institut Agama Islam Ngawi, 2023)
Parents have the role of the first educators for their children in directing, introducing, and implementing Islamic education in their daily lives. However, many parents still feel confused and burdened with their children's care and education while studying at home, especially working parents. Therefore, this study aims to provide understanding to parentsregarding the application of educational methods according to Islamic teachings. This research method is library research using thematically structured data collection techniques and qualitative descriptive analysis tecgniques. In this study, the results of the interaction between parent and child formed a strong personality and character, using methods adapted to their circumstances and conditions. The teaching methods can be applied through advice, examples, habits, and stories. This can certainly produce children who are faithful, sensible, insightful, virtuous, and noble character for the benefit of others and it is hoped that as long as these children study at home, their development can be carried out optimally.